Projection for new city future scenarios – A case study for Kuwait. Issue 3 (March 2018) - Alghais, Nayef; Pullar, David
Abstract: The creation of new cities is a planning approach adopted in several regions around the world, in order to accommodate urban growth. New cities are typically constructed according to well-thought out, centralised plans in areas without any prior development. However, whether the development of these new cities is able to address existing urban issues more effectively than traditional methods such as intensification, is currently an unanswered research question. Several Arabian Gulf countries, such as Kuwait are considering the construction of new cities to address urban issues, specifically the traffic congestion and housing shortages. In Kuwait, the master plan for these construction projects was developed solely by state authorities without any public participation or urban modelling that may have provided a more well-rounded view of the potential impacts and effectiveness. This paper aims to address these research opportunities of investigating the effectiveness of new cities in addressing traffic congestion and housing shortage, as well as the potential to integrate public opinions in urban development in the form of a model. Towards that end, the study proposes an Agent Based Model (ABM) that will allow simulating the population distribution and urban growth impacts of new cities in Kuwait by 2050. The methodology involves collecting primary data via interviewing the key government stakeholders of urban development and surveying the residents in order to collect the model inputs. In Kuwait's society, citizens and non-citizens form two distinct resident groups with often very diverse needs and lifestyles; hence the survey responses will differentiate between them. The data from the interviews and surveys from both resident groups will be incorporated as agent behaviours in the ABM. The simulations examine a multitude of scenarios for the new cities, involving construction delays and infrastructure project delays. The results indicate that the impacts of constructing new cities will be favourable across all different scenarios in terms of alleviating the traffic congestion and housing shortage compared to a business as usual approach of existing urban centre expansion. Furthermore, the survey responses confirm that the resident perspectives closely align with the government's priorities in the master plan for the new cities, further improving the chances for the successful project implementation. The methodology and findings may be applied in cities in the Gulf area or elsewhere with similar urban issues.